93‐4: Evaluation Method and Results for Measuring Stretchability of Two‐Dimensional Stretchable Displays - Lim, Myung Sub; Park, Chan Il; Jung, Haeyoon; Min, Sung Joon; Kim, Taehyun; Song, Jun Hyuk; Oh, Yeonjun; Lee, Injun; Jeong, Yu Ra; Kim, Dojoong; Kim, Aesun; Lee, Hyokang; et al. (SID International Symposium Digest of technical papers, 2024)
We report a highly stretchable display panel capable of enduring extreme deformations including large curvature folding, fully folded deformation and stretching without any damage. We examined both uniaxial and multi‐axial stretching with the panel, and presented a method to calculate its stretchability. Our display panel exhibited areal stretchability of up to 45% strain and remained reliably functional through 10,000 repeated stretching cycles at 20% uniaxial tensile strain. By demonstrating the ability to withstand extreme deformations while maintaining structural integrity, this platform showed strong potential for use in a variety of stretchable displays.